A molecular dynamics investigation on CO2–H2O–CH4 surface tension and CO2–CH4–H2O–graphite sheet contact angles - Yong, Wei; Wei, Zhi-jie; Liu, Yu-yang; Wang, De-qiang; Cui, Yong-zheng (Frontiers in Energy Research, 2023)
Introduction: We perform molecular dynamics (MD) simulations of nanoscopic liquid water drops on a graphite substrate mimicking the carbon-rich pore surface in the presence of CH4/CO2 mixtures at temperatures in the range 300 K–473 K. Methods: The surface tension in MD simulation is calculated via virial expression, and the water droplet contact angle is obtained through a cylindric binning procedure. Results: Our results for the interfacial tension between water and methane as a function of pressure and for the interfacial tension between water and CH4/CO2 mixtures as a function of their composition agree well with the experimental and computational literature. Discussion: The modified Young’s equation has been proven to bridge the macroscopic contact angle and microscopic contact with the experimental literature. The water droplet on both the artificially textured surface and randomly generated surface exhibits a transition between the Wenzel and Cassie–Baxter states with increased roughness height, indicating that surface roughness enhances the hydrophobicity of the solid surface.